2018
DOI: 10.11114/jets.v6i7.3219
|View full text |Cite
|
Sign up to set email alerts
|

Academicians’ Burnout, Vigor and Occupational Satisfactions in the Department of Fine Arts Education: A Sample of Uludag University

Abstract: The success of an educational institution is heavily based on instructors’ occupational satisfaction and their happiness at their workplace. Therefore, determining the case of the instructors’ wellbeing in order to improve working standards is really important to sustain high quality in education. In this sense, this study set out to identify state of academicians in terms of their level of burnout, vigor and occupational satisfaction at a department of Fine Arts Education at Uludag University. All 42 academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…This means that as the level of burnout increase, the level of vigor and educational satisfaction decrease. In the literature, studies indicated that burnout has negative effect on vigor [35,42]. This recent study's findings are parallel with the literature.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This means that as the level of burnout increase, the level of vigor and educational satisfaction decrease. In the literature, studies indicated that burnout has negative effect on vigor [35,42]. This recent study's findings are parallel with the literature.…”
Section: Resultssupporting
confidence: 82%
“…Table 3 shows that for both music and art students, gender did not have any significant effect on SMBM, SMVM and ES scores, p>0.05. In the literature, there are some studies that show females have more burnout and less vigor, and in some studies there is no significant difference [35]. In this study, female and male students seemed to have similar levels of burnout, vigor and educational satisfaction.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…The later attributed it to career change, responsibility over family, as well as workload imparted on them from various obligations. However, a study by Demirbatir and Engür (2018) show no significant difference in age group between any dimensions of their study on academics. In terms of gender, previous studies (like, Bayram et al , 2010; Demirbatir and Engür, 2018; Henny et al , 2014) discovered that female lecturers are more prone to stress than their male counterparts.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Workload included teaching, scholarship and service commitments. In a study of fine arts faculty in Turkey, Demirbatir and Engür (2019) found that health status affects fatigue, job satisfaction and burnout. Whereas Martini et al (2019) found with Italian university faculty that increased student demands can be emotionally exhausting, and that positive student support was ‘associated with higher levels of engagement’ (p. 4).…”
Section: Introductionmentioning
confidence: 99%